2008
DOI: 10.1111/j.1567-1364.2008.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of  fermentation aroma compounds bySaccharomyces cerevisiaewine yeasts: effects of yeast assimilable nitrogen on two model strains

Abstract: The contribution of yeast fermentation metabolites to the aromatic profile of wine is well documented; however, the biotechnological application of this knowledge, apart from strain selection, is still rather limited and often contradictory. Understanding and modeling the relationship between nutrient availability and the production of desirable aroma compounds by different strains must be one of the main objectives in the selection of industrial yeasts for the beverage and food industry. In order to overcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
139
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(154 citation statements)
references
References 38 publications
13
139
1
1
Order By: Relevance
“…Nitrogen concentration will also affect ester formation, as fusel alcohols are precursors for acetate esters (Saerens et al 2010). However, most studies investigating a link between nitrogen supplementation and the production of aroma compounds during fermentation have been conducted in synthetic media or model grape juice (Hernandez-Orte et al 2006, Carrau et al 2008), which may not reflect the conditions in a more complex starting matrix. Although the genes regulating fusel alcohol and ester production in laboratory strains and synthetic media are well known, little is known about nitrogen regulation in commercially relevant strains under production conditions.…”
Section: Impact Of Starting Materials On Production Of Flavor Componentsmentioning
confidence: 99%
“…Nitrogen concentration will also affect ester formation, as fusel alcohols are precursors for acetate esters (Saerens et al 2010). However, most studies investigating a link between nitrogen supplementation and the production of aroma compounds during fermentation have been conducted in synthetic media or model grape juice (Hernandez-Orte et al 2006, Carrau et al 2008), which may not reflect the conditions in a more complex starting matrix. Although the genes regulating fusel alcohol and ester production in laboratory strains and synthetic media are well known, little is known about nitrogen regulation in commercially relevant strains under production conditions.…”
Section: Impact Of Starting Materials On Production Of Flavor Componentsmentioning
confidence: 99%
“…However, for some strains, nitrogen addition at the beginning of fermentation, particularly in nitrogen-rich media, does not necessarily enhance growth (12). Addition of nitrogen also influences the organoleptic characteristics of wine, because it affects the formation of glycerol, organic acids, and volatile compounds (9,10,(13)(14)(15)(16)(17). Unfortunately, much of the information available about the effects of nitrogen addition on metabolism is contradictory, probably due to the different conditions used in the relevant studies.…”
mentioning
confidence: 98%
“…This volatile compound has contributed to fragrance formation in silage through involvement of enzymatic activity for synthesizing aromatic compound/flavoring substances in silage. Carrau et al (2008) reported that aromatic compound i.e. esters, alcohols, acids and lactones as component of flavor in fermented products of grape juice can be produced by S. cerevisiae.…”
Section: Palatability Of Silagementioning
confidence: 99%